2007
DOI: 10.1002/adem.200600232
|View full text |Cite
|
Sign up to set email alerts
|

The Physical Nature of Materials Strengths

Abstract: The strength of a material is assessed most often by means of a tensile test. For a given material with an original cross-section area A 0 , if the applied maximum tensile force is equal to F max , the fracture strength can be calculated by r F =F max /A 0 , as described in the textbooks. [1,2] For a bulk metallic glassy specimen, it often fails in a shear mode, as shown in Figure 1, and the shear fracture surface makes an angle of h T =56°with respect to the tension axis. Such shear fracture behavior has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…13,39 For some Mg-, Co-, and Ti-based metallic glasses, it was found that they often failed in a fragmentation mode or distensile fracture [40][41][42][43][44][45] rather than in the conventional shear fracture mode. [46][47][48][49] Figure 7͑b͒ shows the top view of the fracture surface. The fracture surface does not exhibit shear stress plane, and three distinct regions marked as I, II, and III can be clearly seen.…”
Section: -3mentioning
confidence: 99%
“…13,39 For some Mg-, Co-, and Ti-based metallic glasses, it was found that they often failed in a fragmentation mode or distensile fracture [40][41][42][43][44][45] rather than in the conventional shear fracture mode. [46][47][48][49] Figure 7͑b͒ shows the top view of the fracture surface. The fracture surface does not exhibit shear stress plane, and three distinct regions marked as I, II, and III can be clearly seen.…”
Section: -3mentioning
confidence: 99%
“…To assess the notch effect, one often uses the term of the notch strength ratio (NSR), which is the ratio of the ultimate tensile strength (UTS) of notched sample to the unnotched sample . The materials with NSR >1 normally behave in a “notch strengthening” manner; such materials include common crystalline metals like annealed Cu, steels, and aluminum alloys, while the materials with NSR <1, like ceramics and oxidation glasses, are very sensitive to notches and exhibit a “notch weakening” effect . Here, the NSRs for PMMA with V‐ and U‐notched specimens are 0.26 and 0.24, respectively, much smaller than 1, indicating that both of notches are detrimental to the load carrying ability of PMMA components.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9] The diffusion-multiple approach has been developed to map phase diagrams using assembly of three or more bulk metal pieces. 10,11 In thin film composition spreads, large fractions of compositional phase diagrams can be mapped out with a high density of data points on an individual wafer. The large number of data points can truly bring out the strength of the spread technique because systematic mapping can reveal subtle composition dependence effects which are otherwise very difficult to discern from individual sample experiments with sparse sampling in composition space.…”
Section: Data Management and Visualization Of X-ray Diffraction Spectmentioning
confidence: 99%